Method for converting waste wind power blade composite material into silicon carbide

By mixing waste wind power blade composite powder with conductive agent and performing flash Joule heat treatment, it is directly converted into high value-added silicon carbide, the problem of recycling of retired wind power blade composite materials is solved, and efficient recycling of resources and sustainable environmental development is achieved.

CN119873825AActive Publication Date: 2025-04-25TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202411810133.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-25
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle and process retired wind power blade composite materials, resulting in waste of resources and environmental pollution.

Method used

By mixing the waste wind blade composite powder with conductive agent and performing flash Joule heat treatment, it is directly converted into high value-added silicon carbide.

Benefits of technology

It realizes efficient recycling of waste wind power blade composite materials, reduces energy consumption and greenhouse gas emissions, simplifies process flow, and promotes the sustainable development of the industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873825A_ABST
    Figure CN119873825A_ABST
Patent Text Reader

Abstract

The invention discloses a method for converting a waste wind power blade composite material into silicon carbide, which comprises the following steps: mixing waste wind power blade composite material powder with a conductive agent to obtain a mixture, the waste wind power blade composite material comprising a silicon element and a carbon element; and performing flash Joule heat treatment on the mixture to obtain the silicon carbide. According to the method, the waste wind power blade composite material powder does not need to be subjected to any pretreatment such as pyrolysis, the waste wind power blade composite material can be converted into the silicon carbide with the high additional value only through one-step flash Joule heat treatment in the presence of the conductive agent, and the process steps are simple; and meanwhile, the flash Joule heat treatment is an electric heating pulse rapid high-temperature treatment mode, so that the time consumption is very short, and the method is energy-saving, efficient and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource recycling, and in particular to a method for converting waste wind turbine blade composite materials into silicon carbide. Background Art

[0002] As a representative of new energy, wind power generation has significant advantages. With the advent of the retirement tide of wind power equipment, the recycling of retired wind power equipment faces huge challenges. With the trend of large-scale wind turbines, wind turbine blades are getting longer, towers are getting taller, and single units are getting larger. The weight of the blade hub and the overall proportion are rising simultaneously. Wind turbine blades and related fiberglass products are the most difficult parts of the units and supporting facilities to recycle, which further increases the difficulty of recycling. Although both the industry and academia are working hard to explore diversified recycling technology paths, in actual conditions, no effective method has yet been formed. At present, the most commonly used treatment methods are landfill, incineration, pyrolysis or dissolution, but these methods have problems such as environmental pollution, high carbon emissions, waste of resources, and complex processes. Therefore, the development of a treatment technology with simple process, energy-saving and high efficiency, and environmentally friendly can not only realize the resource utilization and harmlessness of waste wind turbine blade composite materials, but also promote the sustainable development of the industry. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present invention is to propose a method for converting waste wind turbine blade composite materials into silicon carbide, which is simple in process, energy-efficient and environmentally friendly.

[0004] Specifically, the present invention provides a method for converting waste wind turbine blade composite materials into silicon carbide, comprising the following steps:

[0005] Mixing waste wind turbine blade composite material powder with a conductive agent to obtain a mixture, wherein the waste wind turbine blade composite material contains silicon and carbon;

[0006] The mixture is subjected to flash Joule heat treatment to obtain silicon carbide.

[0007] The method of the present invention does not require any pretreatment of the waste wind turbine blade composite material powder, such as pyrolysis, etc. In the presence of a conductive agent, only one step of flash Joule heat treatment is required to convert the waste wind turbine blade composite material into silicon carbide with high added value. The process steps are simple. At the same time, flash Joule heat treatment is a rapid high-temperature treatment method of electric thermal pulses, so it takes very little time, is energy-saving, efficient and environmentally friendly.

[0008] Compared with traditional treatment methods, the method of the present invention can significantly reduce energy consumption, greenhouse gas emissions and solvent use, and simplify the process flow. The method of the present invention can recycle and upgrade waste wind turbine blade composite materials into high-value-added silicon carbide materials, which can reduce production costs and promote the green development of the industry, and has important application prospects. Therefore, the method of the present invention provides a feasible method for the sustainable utilization of waste wind turbine blade composite materials, and can contribute to the development of clean production and circular economy.

[0009] According to some embodiments of the present invention, the waste wind turbine blade composite material includes one or more of glass fiber reinforced plastic and glass fiber reinforced resin.

[0010] According to some embodiments of the present invention, the temperature of the flash Joule heat treatment is 1500° C.-2500° C., and the total time of the flash Joule heat treatment is 0.5 s-2 min.

[0011] According to some embodiments of the present invention, the flash Joule heat treatment is performed using a capacitive pulse, and the flash Joule heat treatment includes a first stage of flash Joule heat treatment and a second stage of flash Joule heat treatment, wherein the voltage and discharge time of the first stage of flash Joule heat treatment are both smaller than those of the second stage of flash Joule heat treatment; preferably, the voltage of the first stage of flash Joule heat treatment is 40V-60V, and the discharge time is 0.4s-1.0s; the voltage of the second stage of flash Joule heat treatment is 130V-150V, and the discharge time is 1s-3s.

[0012] According to some embodiments of the present invention, the flash Joule heat treatment is performed using a DC pulse, and the flash Joule heat treatment includes a first stage of flash Joule heat treatment and a second stage of flash Joule heat treatment, and the voltage, current and discharge time of the first stage of flash Joule heat treatment are all smaller than those of the second stage of flash Joule heat treatment; preferably, the voltage of the first stage of flash Joule heat treatment is 15V-25V, the current is 15A-25A, and the discharge time is 0.4s-1.0s; the voltage of the second stage of flash Joule heat treatment is 28V-35V, the current is 60A-70A, and the discharge time is 10s-20s.

[0013] According to some embodiments of the present invention, the flash Joule heat treatment is performed under vacuum or inert atmosphere; preferably, the flash Joule heat treatment is performed under vacuum; preferably, the vacuum degree is below 10 Pa.

[0014] According to some embodiments of the present invention, the conductive agent includes one or more of conductive carbon black, graphite powder, graphene, carbon nanotubes, petroleum coke, metallurgical coke, coke, and carbon fiber; preferably, the conductive agent includes one or more of graphene and carbon nanotubes.

[0015] According to some embodiments of the present invention, the conductive agent accounts for 20%-50% by mass in the mixture.

[0016] According to some embodiments of the present invention, the mesh size of the waste wind turbine blade composite material powder is 100-500 meshes.

[0017] According to some embodiments of the present invention, the method further comprises post-processing the silicon carbide; the post-processing comprises a purification process; the purification process comprises: pickling to remove metal impurities, and / or roasting to remove carbon.

[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a process flow chart of converting waste wind turbine blade composite materials into silicon carbide according to an embodiment of the present invention.

[0020] Figure 2 This is a picture of the coarse tailings produced during the production of wind turbine blades;

[0021] Figure 3 This is a picture of the fine tailings produced during the production of wind turbine blades;

[0022] Figure 4 This is a picture of a mixture of ground fine tailings and conductive carbon black in Example 1;

[0023] Figure 5 This is a picture of a mixture of ground fine tailings and conductive carbon black loaded into a quartz reaction tube in Example 1;

[0024] Figure 6 The temperature line diagram of the ground fine tailings and conductive carbon black mixture in Example 1 after the first stage of flash Joule heat treatment;

[0025] Figure 7 The temperature line diagram of the ground fine tailings and conductive carbon black mixture in Example 1 after the second stage of flash Joule heat treatment;

[0026] Figure 8 This is a picture of the ground fine tailings and conductive carbon black mixture in Example 1 after two-stage flash Joule heat treatment;

[0027] Fig. 9 The XRD spectrum of the fine tailings produced in the production process of wind turbine blades in Example 1;

[0028] Fig.10The XRD spectrum of the ground fine tailings and conductive carbon black mixture in Example 1 after two-stage flash Joule heat treatment;

[0029] Fig.11 This is a TGA spectrum of the fine tailings generated in the production process of wind turbine blades in Example 1 measured in an air atmosphere;

[0030] Fig.12 This is the C, H, and N element analysis spectrum of the fine tailings generated during the production process of wind turbine blades in Example 1;

[0031] Fig.13 This is the XRF spectrum of the fine tailings generated during the production process of wind turbine blades in Example 1;

[0032] Fig.14 The XRF spectrum of the product obtained by flash Joule heat treatment of the fine tailings and conductive carbon black after grinding in Example 1;

[0033] Fig.15 This is the XRF spectrum of the product in Example 1 after acid washing;

[0034] Fig.16 This is a picture of a mixture of ground fine tailings and conductive carbon black loaded into a quartz tube in Example 2;

[0035] Fig.17 is a temperature diagram of the ground fine tailings and conductive carbon black mixture in Example 2 when subjected to the second stage of flash Joule heat treatment;

[0036] Fig.18 This is a picture of the ground fine tailings and conductive carbon black mixture in Example 2 after two-stage flash Joule heat treatment;

[0037] Fig.19 The Raman spectrum of the product of the mixture of ground fine tailings and conductive carbon black in Example 2 after two-stage flash Joule heat treatment;

[0038] Fig. 20 This is a picture of the coarse material obtained after the retired wind turbine blades were crushed in Example 3;

[0039] Fig.21 This is a picture of the fine powder obtained after grinding the retired wind turbine blades in Example 3;

[0040] Fig. 22 This is a picture of a mixture of retired wind turbine blade fine powder and conductive carbon black in Example 3;

[0041] Fig.23 This is a picture of a mixture of retired wind turbine blade fine powder and conductive carbon black loaded into a quartz tube in Example 3;

[0042] Fig.24The temperature line diagram of the mixture of retired wind turbine blade fine powder and conductive carbon black in Example 3 when subjected to the first stage of flash Joule heat treatment;

[0043] Fig.25 The temperature line diagram of the mixture of retired wind turbine blade fine powder and conductive carbon black in Example 3 after the second stage of flash Joule heat treatment;

[0044] Fig.26 This is a picture of the mixture of retired wind turbine blade fine powder and conductive carbon black in Example 3 subjected to two-stage flash Joule heat treatment;

[0045] Fig. 27 The XRD spectrum of the product of the mixture of retired wind turbine blade fine powder and conductive carbon black after two-stage flash Joule heat treatment in Example 3;

[0046] Fig.28 This is the TGA spectrum of the fine powder of retired wind turbine blades in Example 3;

[0047] Fig.29 This is the XRF spectrum of the fine powder of retired wind turbine blades in Example 3;

[0048] Fig.30 This is the SEM spectrum of the product after the reaction of the retired wind turbine blade fine powder and the conductive carbon black mixture in Example 3;

[0049] Fig.31 This is an enlarged SEM photo of the product after the reaction of the retired wind turbine blade fine powder and the conductive carbon black mixture in Example 3;

[0050] Fig.32 for Fig.30 Element distribution diagram of C in the corresponding area;

[0051] Fig.33 for Fig.30 Element distribution diagram of Si in the corresponding area;

[0052] Fig.34 for Fig.31 Element distribution diagram of O in the corresponding area;

[0053] Fig.35 This is the XRD spectrum of the product of the reaction of the retired wind turbine blade fine powder and the conductive carbon black mixture after calcination treatment in Example 4. DETAILED DESCRIPTION

[0054] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0055] Wind turbine blades are mainly made of glass fiber reinforced plastic. Glass fiber reinforced plastic has the advantages of light weight, good chemical stability, and excellent mechanical properties. It is now widely used in various platforms such as sports equipment, wind turbine blades, automotive industry, aerospace industry, etc. Whether in the processing of glass fiber reinforced plastic products or after the retirement of glass fiber reinforced plastic products, a large amount of waste and tailings will be generated. At present, the most commonly used treatment methods are landfill, incineration, pyrolysis or dissolution, but these methods have problems such as environmental pollution, high carbon emissions, waste of resources, and complex processes. Therefore, the development of a treatment technology with simple process, energy saving and high efficiency, and environmental friendliness can not only realize the resource utilization and harmlessness of waste wind turbine blade composite materials, but also promote the sustainable development of the industry.

[0056] In order to solve the above problems, the present invention proposes a method for converting waste wind turbine blade composite materials into silicon carbide. The method does not require any pretreatment of the waste wind turbine blade composite material powder, such as pyrolysis, etc. In the presence of a conductive agent, only one step of flash Joule heat treatment is required to convert the waste wind turbine blade composite material into silicon carbide with high added value. The process steps are simple. At the same time, flash Joule heat treatment is an electric thermal pulse rapid high-temperature treatment method, so it takes very little time, is energy-saving, efficient and environmentally friendly.

[0057] Specifically, the present invention provides a method for converting waste wind turbine blade composite materials into silicon carbide, comprising the following steps:

[0058] Mixing waste wind turbine blade composite material powder with a conductive agent to obtain a mixture, wherein the waste wind turbine blade composite material contains silicon and carbon;

[0059] The mixture is subjected to flash Joule heat treatment to obtain silicon carbide.

[0060] Since the composite material of waste wind turbine blades contains silicon and carbon, that is, it contains silicon source and carbon source, during the flash Joule heat treatment process, the conductive agent generates high temperature through electric current heating, which can quickly heat the target material and make the silicon and carbon react quickly to generate silicon carbide. This process does not require the use of any additional silicon source and carbon source, only the addition of conductive agent is required, which makes full use of the carbon and silicon in the composite material of waste wind turbine blades and fully realizes the recycling and upgrading of waste materials. In addition, this process does not require the use of any additional solvents and catalysts, and can achieve effects that cannot be achieved by traditional treatment methods.

[0061] Compared with traditional treatment methods, the method of the present invention can significantly reduce energy consumption, greenhouse gas emissions and solvent use, and simplify the process flow. The method of the present invention can recycle and upgrade waste wind turbine blade composite materials into high-value-added silicon carbide materials, which can reduce production costs and promote the green development of the industry, and has important application prospects. Therefore, the method of the present invention provides a feasible method for the sustainable utilization of waste wind turbine blade composite materials, and can contribute to the development of clean production and circular economy.

[0062] In the present invention, "waste wind turbine blade composite material" refers to abandoned or retired wind turbine blade composite material. "Wind turbine blade composite material" refers to a composite material that can be used to prepare wind turbine blades, which contains silicon and carbon. For example, the wind turbine blade composite material includes a composite material of silicon dioxide and a polymer material. The polymer material includes plastics, resins, etc.

[0063] The waste wind turbine blade composite material may be various types of wind turbine blade composite materials, for example, excess and residual materials caused by cutting, processing and other processes during the production of wind turbine blades, such as Figure 2 and 3 As shown, the wind turbine blade composite materials have been retired after reaching their service life, or the wind turbine blade composite materials have not reached their retirement age but have been damaged or eliminated during use.

[0064] In some embodiments, the waste wind turbine blade composite material includes one or more of glass fiber reinforced plastic and glass fiber reinforced resin. The main raw material of wind turbine blades is glass fiber reinforced plastic. Glass fiber reinforced plastic is a strong composite material with glass fiber (main component SiO2) and its products as reinforcing materials and synthetic resin as matrix material. The silicon element of the waste wind turbine blade composite material mainly comes from glass fiber, and the carbon element mainly comes from synthetic resin. The inventors found that when the conductive agent is heated by electric current to generate high temperature, the silicon element in the glass fiber and the carbon element in the synthetic resin (the carbon element is mainly in a lower valence state such as 0 valence and / or negative valence) can directly undergo carbon thermal reduction reaction to generate silicon carbide without pre-treating the waste wind turbine blade composite material powder, for example, there is no need to pre-pyrolyze the composite material to form a carbon element that can react with silicon element, etc. The valence state of carbon element in synthetic resin is even lower than that of carbon in carbon element, which is more conducive to the reaction, thereby simplifying the process flow and reducing costs.

[0065] In some embodiments, the waste wind turbine blade composite material powder can be obtained by cutting, crushing, grinding, etc., of the waste wind turbine blade composite material. These physical operations are conventional operations in the art and are not specifically limited here.

[0066] In some embodiments, the temperature of the flash Joule heat treatment may be 1500-2500°C, and the total time of the flash Joule heat treatment may be 0.5s-2min. The temperature can be quickly brought to 1500-2500°C by adjusting the pulse electrothermal parameters. Optimizing the temperature and time of the flash Joule heat treatment is beneficial to promoting the reaction of silicon and carbon and reducing the occurrence of side reactions. The flash Joule heat treatment of the present invention is a rapid high-temperature treatment of electric heat pulses. The desired temperature can be quickly reached by adjusting the pulse electrothermal parameters.

[0067] In some specific embodiments, the temperature of the flash Joule heat treatment may be 1500°C-2000°C, 2000°C-2500°C, 1700°C-2000°C, 2000°C-2200°C or 1700°C-2200°C.

[0068] In some specific embodiments, the total time of the flash Joule heat treatment can be 0.5 s, 1 s, 2 s, 3 s, 4 s, 5 s, 6 s, 7 s, 8 s, 9 s, 10 s, 20 s, 30 s, 40 s, 50 s, 60 s, 70 s, 80 s, 90 s, 100 s, 110 s, or 120 s.

[0069] The total time of the flash Joule heat treatment is the sum of all discharge times during the entire heat treatment process. For example, if two pulse discharges are performed during the entire heat treatment process, the total time of the flash Joule heat treatment is the sum of the two discharge times.

[0070] In some embodiments, the flash Joule heat treatment includes: loading the mixture of the waste wind turbine blade composite material powder and the conductive agent into a reactor, and placing the reactor as a whole in a vacuum or inert atmosphere; connecting electrodes at both ends of the reactor to access a pulse current system; and passing a pulse current to perform flash Joule heat treatment. The reactor may include a variety of materials, such as quartz, mullite, etc. The material of the electrode may include graphite. The pulse current system can generate electric pulses at the second level, with controllable time and controllable current.

[0071] In some embodiments, the flash Joule heat treatment is performed using a capacitor pulse, and the flash Joule heat treatment includes a first stage of flash Joule heat treatment and a second stage of flash Joule heat treatment, wherein the voltage and discharge time of the first stage of flash Joule heat treatment are both shorter than those of the second stage of flash Joule heat treatment. Using segmented heat treatment and controlling the voltage and discharge time of the first stage to be shorter than that of the second stage is beneficial to improving the conversion rate of silicon carbide by more than 25% compared with non-segmented heat treatment.

[0072] In the present invention, the capacitive pulse is a pulse emitted by a capacitor, and the "voltage" here refers to the voltage of the capacitor.

[0073] In the present invention, the discharge time refers to the duration of releasing electric energy in the form of pulses.

[0074] In some specific embodiments, the voltage of the first stage of flash Joule heat treatment is 40V-60V, and the discharge time is 0.4s-1.0s; the voltage of the second stage of flash Joule heat treatment is 130V-150V, and the discharge time is 1s-3s. Optimizing the voltage and discharge time of the first stage of heat treatment and the voltage and discharge time of the second stage of heat treatment is conducive to further improving the conversion rate of silicon carbide. The higher the voltage, the higher the heat treatment temperature, and the more complete the reaction. The first stage of heat treatment is carried out at a lower temperature, and a pre-reaction is carried out first. The second stage of heat treatment increases the temperature to allow the reaction to proceed fully.

[0075] In some specific embodiments, the first stage of flash Joule heat treatment includes: performing treatment continuously for 1 to 4 times at a voltage of 40V-60V and a discharge time of 0.4s-1.0s; the second stage of flash Joule heat treatment includes: performing treatment continuously for 1 to 3 times at a voltage of 130V-150V and a discharge time of 1s-3s.

[0076] In some specific embodiments, the voltage of the first flash Joule heat treatment may be 40 V, 45 V, 50 V, 55 V or 60 V. The discharge time of the first flash Joule heat treatment may be 0.4 s, 0.5 s, 0.6 s, 0.7 s, 0.8 s, 0.9 s or 1.0 s. "Continuously performing 1 to 4 treatments" means that the mixture is subjected to 1, 2, 3 or 4 pulse discharges at a predetermined voltage and a predetermined discharge time.

[0077] In some specific embodiments, the voltage of the second flash Joule heat treatment may be 130 V, 135 V, 140 V, 145 V or 150 V. The discharge time of the second flash Joule heat treatment may be 1 s, 1.5 s, 2 s, 2.5 s or 3 s. "Continuously performing 1 to 3 treatments" means that the mixture is pulse-discharged once, twice or three times at a predetermined voltage and a predetermined discharge time.

[0078] In some embodiments, the flash Joule heat treatment is performed using a DC pulse, and the flash Joule heat treatment includes a first stage of flash Joule heat treatment and a second stage of flash Joule heat treatment, wherein the voltage, current and discharge time of the first stage of flash Joule heat treatment are all less than those of the second stage of flash Joule heat treatment. Using segmented heat treatment and controlling the voltage, current and discharge time of the first stage to be less than that of the second stage is beneficial to improving the conversion rate of silicon carbide by more than 25% compared with non-segmented heat treatment.

[0079] In the present invention, the DC pulse is a pulse formed by means of a DC power supply, and the voltage here refers to the power supply voltage.

[0080] In some specific embodiments, the voltage of the first stage of flash Joule heat treatment is 15V-25V, the current is 15A-25A, and the discharge time is 0.4s-1.0s; the voltage of the second stage of flash Joule heat treatment is 28V-35V, the current is 60A-70A, and the discharge time is 10s-20s. Optimizing the voltage, current, and discharge time of the first stage of heat treatment and the voltage, current, and discharge time of the second stage of heat treatment is conducive to further improving the conversion rate of silicon carbide. The higher the voltage and current, the higher the heat treatment temperature, and the more complete the reaction. The first stage of heat treatment is carried out at a lower temperature to perform a pre-reaction first, and the second stage of heat treatment increases the temperature to allow the reaction to proceed fully.

[0081] In some specific embodiments, the voltage of the first flash Joule heat treatment is 15 V, 16 V, 17 V, 18 V, 19 V, 20 V, 21 V, 22 V, 23 V, 24 V or 25 V. The current is 15 A, 16 A, 17 A, 18 A, 19 A, 20 A, 21 A, 22 A, 23 A, 24 A or 25 A. The discharge time is 0.4 s, 0.5 s, 0.6 s, 0.7 s, 0.8 s, 0.9 s or 1.0 s.

[0082] In some specific embodiments, the voltage of the second flash Joule heat treatment is 28 V, 29 V, 30 V, 31 V, 32 V, 33 V, 34 V or 35 V. The current is 60 A, 61 A, 62 A, 63 A, 64 A, 65 A, 66 A, 67 A, 68 A, 69 A or 70 A. The discharge time is 10 s, 11 s, 12 s, 13 s, 14 s, 15 s, 16 s, 17 s, 18 s, 19 s or 20 s.

[0083] In some specific embodiments, the first stage of flash Joule heat treatment includes: setting the discharge voltage to 15V-25V, the discharge current to 15A-25A, the discharge time to 0.4s-1.0s, and the number of discharges to 1-4 times; the second stage of flash Joule heat treatment includes: setting the discharge voltage to 28V-35V, the discharge current to 60A-65A, the discharge time to 10s-20s, and the number of discharges to 1-2 times. "The number of discharges to 1-4 times" means that the mixture is pulse-discharged once, twice, three times, or four times at a predetermined voltage, a predetermined current, and a predetermined discharge time. "The number of discharges to 1-2 times" means that the mixture is pulse-discharged once or twice at a predetermined voltage, a predetermined current, and a predetermined discharge time.

[0084] In some embodiments, the flash Joule heat treatment is performed in a vacuum or inert atmosphere. The presence of oxygen will affect the formation of silicon carbide and the progress of the reaction. By evacuating or filling with an inert atmosphere, the influence of oxygen can be reduced.

[0085] In some specific embodiments, the flash Joule heat treatment is performed under vacuum. A higher vacuum degree is conducive to promoting the reaction between silicon and carbon in the waste wind turbine blade composite material powder and improving the conversion rate of silicon carbide. Preferably, the vacuum degree is below 10Pa, for example, below 8Pa or below 5Pa.

[0086] In some specific embodiments, the inert atmosphere includes one or more of nitrogen, argon, and the like.

[0087] In some embodiments, the conductive agent includes one or more of conductive carbon black, graphite powder, graphene, carbon nanotubes, petroleum coke, metallurgical coke, coke, and carbon fiber. Preferably, the conductive agent includes one or more of graphene and carbon nanotubes. Graphene and carbon nanotubes have better conductivity. The better the conductivity, the more conducive it is to generate high temperature through electric current heating, which is conducive to shortening the time consumption. Conductive carbon black and graphite powder have good conductivity and low cost, and they also have advantages in actual production.

[0088] In some embodiments, the purity of the conductive agent is 95%-99%, such as 95%, 96%, 97%, 98% or 99%. A high-purity conductive agent is beneficial to reduce the introduction of impurities.

[0089] In some embodiments, the mass proportion of the conductive agent in the mixture is 20%-50%. "The mass proportion of the conductive agent in the mixture" refers to the ratio of the mass of the conductive carbon black to the total mass of the mixture. Optimizing the amount of conductive agent is conducive to shortening the time and improving the conversion rate of silicon carbide. If the amount of conductive agent is too small, it will not be able to fully contact with the waste wind turbine blade composite material powder, the heat distribution will be uneven, and some powders may not react.

[0090] In some specific embodiments, the conductive agent accounts for 20%, 25%, 30%, 35%, 40%, 45% or 50% by mass in the mixture.

[0091] In some embodiments, the mesh size of the waste wind turbine blade composite powder is 100-500 meshes. Optimizing the mesh size of the powder is beneficial to promoting the reaction. Generally, the finer the powder, the more conducive to the reaction.

[0092] In some specific embodiments, the mesh size of the waste wind turbine blade composite material powder is 100 mesh, 200 mesh, 300 mesh, 400 mesh or 500 mesh.

[0093] In some embodiments, the method further comprises: performing post-processing on the silicon carbide. The post-processing comprises purification. The purification comprises: acid washing to remove metal impurities, and / or roasting to remove carbon. The post-processing can be selectively performed according to the requirements for the purity of the silicon carbide product.

[0094] In some specific embodiments, the acid includes at least one of an inorganic acid and an organic acid. For example, the inorganic acid includes one or more of sulfuric acid, nitric acid, and hydrochloric acid. For example, the organic acid includes one or more of acetic acid, citric acid, etc. According to the difference in the components of the waste wind turbine blade composite material, the metal impurities include calcium, aluminum, etc.

[0095] In some specific embodiments, the calcination temperature is 600°C-800°C, for example, 600°C, 650°C, 700°C, 750°C or 800°C.

[0096] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0097] Example 1

[0098] The fine tailings generated during the production of wind turbine blades are converted into silicon carbide materials through capacitor pulse discharge. The specific steps are as follows:

[0099] (1) Select the fine tailings produced in the production process of wind turbine blades as raw materials, such as Figure 3 shown.

[0100] (2) Cutting, crushing and grinding the fine tailings from step 1 to obtain waste wind turbine blade composite material powder, wherein the powder has a mesh size of 300 meshes.

[0101] (3) The powder of step 2 is uniformly mixed with the conductive carbon black, specifically, the mixture is mixed by manual grinding to obtain a mixture such as Figure 4 As shown, the mass proportion of conductive carbon black in the mixture is 40%.

[0102] (4) A quartz tube with an inner diameter of 8 mm and a length of 70 mm is used as a reaction tube. A conductive plug (graphite plug) is installed at one end of the quartz tube, and 0.3 g of the powder of step 3 is installed from the other end, and then another conductive plug (graphite plug) is installed to form a relatively closed reaction environment, such as Figure 5 Finally, install the quartz tube on the tube reaction rack (Taiyuan Saiyin New Material Technology Co., Ltd.), rotate the knob on the side of the tube reaction rack to connect the mixed powder to the power supply, detect the sample resistance, compress the reaction tube rack, and observe the resistance value at the same time to reach the required resistance value. The resistance value is 2.0Ω.

[0103] (5) Place the tubular reaction rack in the stainless steel vacuum chamber, align the infrared temperature probe with the reactant in the quartz tube, close the stainless steel vacuum chamber, and start the vacuum pump to achieve the required vacuum degree within 10Pa.

[0104] (6) Electrodes are connected to both ends of the quartz tube to access the capacitor pulse current system (Taiyuan Saiyin New Material Technology Co., Ltd.). Within the withstand voltage range, the charge of the capacitor is proportional to the capacitor voltage. The maximum capacitor voltage of the instrument used in this experiment is 300V.

[0105] (7) Pass a pulse current to perform flash Joule heat treatment. Specifically, a two-stage flash Joule heat treatment mode is used; the first stage: set the voltage to 50V, the discharge time to 0.5s, and perform three consecutive treatments; the second stage: set the voltage to 140V, the discharge time to 2s, and perform two consecutive treatments. While the Joule heat reaction is taking place, start the temperature acquisition software to measure the temperature. After the reaction is completed, stop collecting data and record it in time, and save the data. The temperature curves of the two-stage flash Joule heat treatment are as follows: Figure 6 , Figure 7 After the heat treatment, the product obtained by the reaction is as shown Figure 8 According to the XRD results, the conversion rate of silicon carbide is more than 90%.

[0106] (8) Characterization of the fine tailings raw materials and the products after the reaction includes: X-ray diffraction (XRD), thermogravimetric analysis (TGA), and X-ray fluorescence spectroscopy (XRF). XRD characterization shows that the main component of the fine tailings is amorphous silicon dioxide ( Fig. 9 ), the fine tailings are quickly treated at high temperature and converted into silicon carbide ( Fig.10 ). TGA characterization shows that the organic component epoxy resin in the fine tail material accounts for about 20% by weight ( Fig.11 ). Elemental analysis shows that the mass percentage of C element in the fine tailings is about 15% ( Fig.12 ). XRF characterization shows that the fine tailings contain about 35% Ca and 35% Si, and also contain other metal elements ( Fig.13 ). The element content of the reaction product is as follows Fig.14 As shown, the mass proportions of the various components are: Si element accounts for about 39%, Ca element accounts for about 29%, Al element accounts for about 10%, Mg element accounts for about 9%, and Y element accounts for about 5%.

[0107] (9) Take out the product of step 7, grind it into fine powder with a mortar, mix the powder with 40mL hydrochloric acid (concentration is 1 mol / L), and heat it in an oil bath at 80°C for 2 hours. After pickling, the mass proportion of Si element is about 74%, the mass proportion of Ca element is about 10%, and it also contains a small amount of other metal elements ( Fig.15).

[0108] Example 2

[0109] The fine tailings generated during the production of wind turbine blades are converted into silicon carbide materials through DC pulse discharge. The specific steps are as follows:

[0110] Steps (1) to (5) are the same as those of Example 1, except that the amount of the mixture in the quartz tube in step (4) is 1.2 g. Fig.16 As shown in the figure, the resistance value of the mixture in the tube after compression is 3.0Ω.

[0111] (6) Electrodes were connected to both ends of the quartz tube, thereby connecting it to a DC pulse discharge system (Taiyuan Saiyin New Material Technology Co., Ltd.), with a maximum current of 83A and a maximum voltage of 36V.

[0112] (7) Set the experimental parameters and start the Joule heating reaction. Specifically, a two-stage flash Joule heating treatment mode is used; the first stage: set the voltage to 20V, set the current to 20A, the discharge time to 0.5s, the interval time to 0.1s, and the number of discharges to 3 times; the second stage: the voltage to 30V, the current to 65A, the discharge time to 15s, and the number of discharges to 1 time. Start the temperature acquisition software to record the data, and control the system to charge and discharge according to the set process. At the same time, monitor the reaction current, voltage and reaction temperature. After the reaction is completed, stop collecting data and save the data in time. The temperature curve of the second stage of flash Joule heating treatment is shown as follows: Fig.17 The product after the reaction is Fig.18 According to the XRD results, the conversion rate of silicon carbide is more than 90%.

[0113] (8) Raman spectroscopy characterization of the reaction products. Raman spectroscopy characterization shows that the fine tailings generated in the production process of wind turbine blades are converted into silicon carbide materials after rapid high-temperature treatment, and graphene materials are also generated at the same time, such as Fig.19 shown.

[0114] Example 3

[0115] The waste wind turbine blades that have reached their service life are converted into silicon carbide materials through capacitor pulse discharge. The specific steps are as follows:

[0116] (1) Select retired wind turbine blades as raw materials.

[0117] (2) Cut, crush and grind the retired wind turbine blades in step 1 to obtain a composite material powder of waste wind turbine blades, wherein the mesh size of the powder is 200 meshes. Fig. 20 As shown in the figure, the photo of the fine powder of retired wind turbine blades obtained after grinding is as follows Fig.21 shown.

[0118] Steps (3) to (7) are the same as steps (3) to (7) of Example 1. The photo of the mixture of the fine powder of retired wind turbine blades and the conductive carbon black is shown in FIG. Fig. 22 The photo of the fine powder of retired wind turbine blades mixed with conductive carbon black and loaded into a quartz tube is shown in Fig.23 The temperature curves of the two-stage flash Joule heat treatment are shown in Fig.24 , Fig.25 The product obtained after the reaction is as shown Fig.26 According to the XRD results, the conversion rate of silicon carbide is more than 90%.

[0119] (8) Characterization of the products before and after the reaction includes: XRD, TGA, XRF, SEM. XRD characterization shows that the fine powder of retired wind turbine blades is successfully converted into silicon carbide material after rapid high temperature treatment ( Fig. 27 ). TGA characterization shows that the epoxy resin mass ratio in the fine powder of retired wind turbine blades is about 53% ( Fig.28 ). XRF characterization shows that the Ca element accounts for about 42% by mass in the fine powder of retired wind turbine blades, the Si element accounts for about 34% by mass, and other metal elements are also contained ( Fig.29 ). SEM characterization shows that the silicon carbide material converted from the fine powder of retired wind turbine blades after rapid high-temperature treatment has a finer powder structure ( Figure 30-Figure 31 ), and elemental analysis also shows that the main components of the converted silicon carbide material are silicon and carbon, while the oxygen content is low ( Fig.32 , Fig.33 , Fig.34 ).

[0120] Example 4

[0121] The product obtained in Example 3 was purified by the following specific steps:

[0122] The product obtained in Example 3 was placed in a muffle furnace for calcination to remove carbon at a temperature of 800°C for 30 minutes, and the sample was taken out after the calcination. The product obtained in Example 3 will contain graphene material, and pure silicon carbide material can be obtained after calcination in a muffle furnace. The process flow chart of Example 4 is shown in FIG. Figure 1 shown.

[0123] The product after calcination is characterized. After calcination, pure silicon carbide material such as Fig.35 According to the XRD characterization results, there are no other impurity peaks in the calcined silicon carbide.

[0124] Example 5

[0125] The method described in Example 1 is followed, except that in step (7), a pulse current is passed to perform flash Joule heat treatment. Specifically, a two-stage flash Joule heat treatment mode is used; in the first stage, the voltage is set to 40V, the discharge time is 0.6s, and the treatment is performed three times in succession; in the second stage, the voltage is set to 130V, the discharge time is 3s, and the treatment is performed twice in succession. While the Joule heat reaction is being carried out, the temperature acquisition software is started to measure the temperature. After the reaction is completed, stop collecting data records in time and save the data. After the heat treatment is completed, the product obtained by the reaction is similar to Figure 8 According to the XRD results, the conversion rate of silicon carbide is over 92%.

[0126] Example 6

[0127] The method described in Example 1 is followed, except that in step (7), a pulse current is passed to perform flash Joule heat treatment. Specifically, a two-stage flash Joule heat treatment mode is used; in the first stage, the voltage is set to 60V, the discharge time is 0.4s, and the treatment is performed three times in succession; in the second stage, the voltage is set to 150V, the discharge time is 1s, and the treatment is performed twice in succession. While the Joule heat reaction is being carried out, the temperature acquisition software is started to measure the temperature. After the reaction is completed, stop collecting data records in time and save the data. After the heat treatment is completed, the product obtained by the reaction is similar to Figure 8 According to the XRD results, the conversion rate of silicon carbide is over 95%.

[0128] Example 7

[0129] The method described in Example 2 is followed, except that (7) the experimental parameters are set and the Joule heat reaction is started. Specifically, a two-stage flash Joule heat treatment mode is adopted; the first stage: the voltage is set to 15V, the current is set to 15A, the discharge time is 0.6s, the interval time is 0.1s, and the number of discharges is 3 times; the second stage: the voltage is 28V, the current is 60A, the discharge time is 20s, and the number of discharges is 1 time. Start the temperature acquisition software for data recording, and control the system to charge and discharge according to the set process. At the same time, monitor the reaction current, voltage and reaction temperature. After the reaction is completed, stop collecting data and save the data in time. According to the XRD results, the conversion rate of silicon carbide is above 92%.

[0130] Example 8

[0131] The method described in Example 2 is followed, except that (7) the experimental parameters are set and the Joule heat reaction is started. Specifically, a two-stage flash Joule heat treatment mode is adopted; the first stage: set the voltage to 25V, set the current to 25A, the discharge time to 0.4s, the interval time to 0.1s, and the number of discharges to 3 times; the second stage: the voltage to 35V, the current to 70A, the discharge time to 10s, and the number of discharges to 1 time. Start the temperature acquisition software to record the data, and control the system to charge and discharge according to the set process. At the same time, monitor the reaction current, voltage and reaction temperature. After the reaction is completed, stop collecting data and save the data in time. According to the XRD results, the conversion rate of silicon carbide is more than 95%.

[0132] Example 9

[0133] The method described in Example 1 is followed, except that in step (7), a pulse current is introduced to perform flash Joule heat treatment. Specifically, a two-stage flash Joule heat treatment mode is adopted; the first stage: set the voltage to 20V, the discharge time to 0.5s, and perform 3 consecutive treatments; the second stage: set the voltage to 80V, the discharge time to 2s, and perform 2 consecutive treatments. While the Joule heat reaction is being carried out, start the temperature acquisition software to measure the temperature, and the maximum temperature is 1000°C. After the reaction is completed, stop collecting data and record it in time, and save the data. The conversion rate of silicon carbide is less than 20%.

[0134] Example 10

[0135] The method described in Example 1 is followed, except that in step (7), a pulse current is introduced to perform flash Joule heat electrothermal treatment. Specifically, a flash Joule heat treatment mode is adopted: the voltage is set to 50V, the discharge time is 0.5s, and the treatment is performed continuously for 11 times. While the Joule heat reaction is being performed, the temperature acquisition software is started to measure the temperature. After the reaction is completed, the data collection and recording is stopped in time and the data is saved. According to the XRD results, the conversion rate of silicon carbide is less than 30%.

[0136] Embodiment 11

[0137] The method described in Example 1 is followed, except that in step (7), a pulse current is introduced to perform flash Joule heat electrothermal treatment. Specifically, a flash Joule heat treatment mode is adopted: the voltage is set to 140V, the discharge time is 2s, and the treatment is performed twice in succession. While the Joule heat reaction is being performed, the temperature acquisition software is started to measure the temperature. After the reaction is completed, the data collection and recording is stopped in time and the data is saved. According to the XRD results, the conversion rate of silicon carbide is less than 60%.

[0138] Embodiment 13

[0139] The method described in Example 1 is followed, except that (7) a pulse current is introduced to perform flash Joule heat treatment. Specifically, a two-stage flash Joule heat treatment mode is adopted; the first stage: the voltage is set to 140V, the discharge time is 2s, and the treatment is performed twice in succession; the second stage: the voltage is set to 50V, the discharge time is 0.5s, and the treatment is performed three times in succession. While the Joule heat reaction is being carried out, the temperature acquisition software is started to measure the temperature. After the reaction is completed, stop collecting data and record it in time, and save the data. According to the XRD results, the conversion rate of silicon carbide is less than 80%.

[0140] Embodiment 14

[0141] The method described in Example 2 is followed, except that in step (7), the experimental parameters are set to start the Joule heat reaction. Specifically, a flash Joule heat treatment mode is adopted: the voltage is set to 20V, the current is set to 20A, the discharge time is 0.5s, the interval time is 0.1s, and the number of discharges is 33 times. The temperature acquisition software is started to record the data, and the control system performs charging and discharging according to the set process. At the same time, the reaction current, voltage and reaction temperature are monitored. After the reaction is completed, stop collecting data and save the data in time. According to the XRD results, the conversion rate of silicon carbide is less than 50%.

[0142] Embodiment 15

[0143] The method described in Example 2 is followed, except that in step (7), the experimental parameters are set to start the Joule heat reaction. Specifically, a flash Joule heat treatment mode is adopted: the voltage is set to 30V, the current is set to 65A, the discharge time is 15s, and the number of discharges is 1. The temperature acquisition software is started to record data, and the control system performs charging and discharging according to the set process. At the same time, the reaction current, voltage and reaction temperature are monitored. After the reaction is completed, stop collecting data and record in time, and save the data. According to the XRD results, the conversion rate of silicon carbide is less than 50%.

[0144] Example 16

[0145] The method described in Example 2 is followed, except that (7) the experimental parameters are set and the Joule heat reaction is started. Specifically, a two-stage flash Joule heat treatment mode is adopted; the first stage: voltage 30V, current 65A, discharge time 15s, discharge number 1 time; the second stage: set the voltage to 20V, set the current to 20A, discharge time 0.5s, interval time 0.1s, and discharge number 3 times. Start the temperature acquisition software for data recording, and control the system to charge and discharge according to the set process. At the same time, monitor the reaction current, voltage and reaction temperature. After the reaction is completed, stop collecting data and save the data. According to the XRD results, the conversion rate of silicon carbide is less than 80%.

[0146] Embodiment 17

[0147] The method described in Example 1 was followed, except that the vacuum degree in step (5) was 30 Pa. According to the XRD results, the conversion rate of silicon carbide was less than 85%.

[0148] Embodiment 18

[0149] The method described in Example 1 was followed, except that graphene was used instead of conductive carbon black. According to the XRD results, the conversion rate of silicon carbide was above 95%.

[0150] Embodiment 19

[0151] The method described in Example 1 was followed, except that carbon nanotubes were used instead of conductive carbon black. According to the XRD results, the conversion rate of silicon carbide was above 92%.

[0152] Embodiment 20

[0153] The method described in Example 1 was followed, except that in step (3), the mass proportion of the conductive carbon black in the mixture was 20%. According to the XRD results, the conversion rate of silicon carbide was above 90%.

[0154] Embodiment 21

[0155] The method described in Example 1 was followed, except that in step (3), the mass proportion of the conductive carbon black in the mixture was 50%. According to the XRD results, the conversion rate of silicon carbide was above 95%.

[0156] Embodiment 22

[0157] The method described in Example 1 was followed, except that in step (3), the mass proportion of the conductive carbon black in the mixture was 10%. According to the XRD results, the conversion rate of silicon carbide was less than 70%.

[0158] Embodiment 23

[0159] The method described in Example 1 was followed, except that in step (3), the mass proportion of the conductive carbon black in the mixture was 60%. According to the XRD results, the conversion rate of silicon carbide was 98%, but the carbon content in the product was relatively high.

[0160] Embodiment 24

[0161] The method described in Example 1 was followed, except that the mesh size of the powder in step (2) was 50 mesh. According to the XRD results, the conversion rate of silicon carbide was less than 60%.

[0162] Comparative Example 1

[0163] The method described in Example 1 was followed, except that silicone rubber (Zhonghao Chenguang Chemical Research Institute Co., Ltd.) was used to replace the fine tailings produced during the production of wind turbine blades. According to the XRD results, the conversion rate of silicon carbide was less than 30%. The conversion rate was low when silicone rubber was treated using the method of the present invention. Although the specific reason is unclear, it is speculated that it may be related to the existence form of silicon element.

[0164] By comparing the embodiments and the comparative examples, it can be seen that the method of the present invention does not require any pretreatment of the waste wind turbine blade composite material powder, such as pyrolysis, and only requires one step of flash Joule heat treatment in the presence of a conductive agent to convert the waste wind turbine blade composite material into silicon carbide with high added value. The process steps are simple, and the flash Joule heat treatment is a rapid high-temperature treatment method of an electric thermal pulse, so it takes very little time, is energy-efficient, efficient, and environmentally friendly.

[0165] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0166] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0167] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for converting waste wind turbine blade composite materials into silicon carbide, characterized in that: The following steps are involved: Mixing waste wind turbine blade composite material powder with a conductive agent to obtain a mixture, wherein the waste wind turbine blade composite material contains silicon and carbon; The mixture is subjected to flash Joule heat treatment to obtain silicon carbide.

2. The method according to claim 1, characterized in that The waste wind turbine blade composite material includes one or more of glass fiber reinforced plastic and glass fiber reinforced resin.

3. The method according to claim 1 or 2, characterized in that: The temperature of the flash Joule heat treatment is 1500° C.-2500° C., and the total time of the flash Joule heat treatment is 0.5 s-2 min.

4. The method according to claim 1 or 2, characterized in that: The flash Joule heat treatment is performed using a capacitor pulse, and the flash Joule heat treatment includes a first stage of flash Joule heat treatment and a second stage of flash Joule heat treatment, wherein the voltage and discharge time of the first stage of flash Joule heat treatment are both shorter than those of the second stage of flash Joule heat treatment; Preferably, the voltage of the first stage of flash Joule heat treatment is 40V-60V, and the discharge time is 0.4s-1.0s; the voltage of the second stage of flash Joule heat treatment is 130V-150V, and the discharge time is 1s-3s.

5. The method according to claim 1 or 2, characterized in that: The flash Joule heat treatment is performed using a DC pulse, and the flash Joule heat treatment includes a first stage of flash Joule heat treatment and a second stage of flash Joule heat treatment, wherein the voltage, current and discharge time of the first stage of flash Joule heat treatment are all smaller than those of the second stage of flash Joule heat treatment; Preferably, the voltage of the first stage of flash Joule heat treatment is 15V-25V, the current is 15A-25A, and the discharge time is 0.4s-1.0s; the voltage of the second stage of flash Joule heat treatment is 28V-35V, the current is 60A-70A, and the discharge time is 10s-20s.

6. The method according to claim 1 or 2, characterized in that: The flash Joule heat treatment is carried out in a vacuum or inert atmosphere; Preferably, the flash Joule heat treatment is performed under vacuum; Preferably, the vacuum degree is below 10 Pa.

7. The method according to claim 1 or 2, characterized in that: The conductive agent includes one or more of conductive carbon black, graphite powder, graphene, carbon nanotubes, petroleum coke, metallurgical coke, coke, and carbon fiber; Preferably, the conductive agent includes one or more of graphene and carbon nanotubes.

8. The method according to claim 1 or 2, characterized in that: The conductive agent accounts for 20%-50% by mass in the mixture.

9. The method according to claim 1 or 2, characterized in that: The mesh size of the waste wind turbine blade composite material powder is 100-500 meshes.

10. The method according to claim 1 or 2, characterized in that: Also includes: Post-processing the silicon carbide; the post-processing includes purification treatment; The purification process includes acid washing to remove metal impurities, and / or roasting to remove carbon.

Citation Information

Patent Citations

  • Method and device for preparing black phosphorus nanoparticles by flash evaporation technology

    CN114804044A

  • Method for rapidly preparing nanoscale short dendrite SiC

    CN119079999A

  • Method of producing silicon carbide

    JP2015166288A

  • Ultrafast flash joule heating synthesis methods and systems for performing same

    US20230374623A1

  • Graphene preparation method

    WO2024010271A1

Cited By

  • Preparation method of silicon-carbon electrode material, silicon-carbon electrode material and application of silicon-carbon electrode material

    CN120288776A

  • A preparation method of silicon-carbon electrode material and silicon-carbon electrode material and application thereof

    CN120288776B

  • Fan blade resource recycling system and method

    CN120382040A

  • Method for recycling glass fibers from waste wind turbine blades

    CN120535825A

  • Method for preparing battery negative hard carbon material by using wind driven generator blade

    CN121672488A